Identifying invasive species threats, pathways, and impacts to improve biosecurity - Deah Lieurance; Susan Canavan; Donald C. Behringer; Amy E. Kendig; Carey R. Minteer; Lindsey S. Reisinger; Christina M. Romagosa; S. Luke Flory; Julie L. Lockwood; Patti J. Anderson; Shirley M. Baker; Jamie Bojko; et al. (Ecosphere, 2023)
Abstract Managing invasive species with prevention and early‐detection strategies can avert severe ecological and economic impacts. Horizon scanning, an evidence‐based process combining risk screening and consensus building to identify threats, has become a valuable tool for prioritizing invasive species management and prevention. We assembled a working group of experts from academic, government, and nonprofit agencies and organizations, and conducted a multi‐taxa horizon scan for Florida, USA, the first of its kind in North America. Our primary objectives were to identify high‐risk species and their introduction pathways, to detail the magnitude and mechanism of potential impacts, and, more broadly, to demonstrate the utility of horizon scanning. As a means to facilitate future horizon scans, we document the process used to generate the list of taxa for screening. We evaluated 460 taxa for their potential to arrive, establish, and cause negative ecological and socioeconomic impacts, and identified 40 potential invaders, including alewife, zebra mussel, crab‐eating macaque, and red swamp crayfish. Vertebrates and aquatic invertebrates posed the greatest invasion threat, over half of the high‐risk taxa were omnivores, and there was high confidence in the scoring of high‐risk taxa. Common arrival pathways were ballast water, biofouling of vessels, and escape from the pet/aquarium/horticulture trade. Competition, predation, and damage to agriculture/forestry/aquaculture were common impact mechanisms. We recommend full risk analysis for the high‐risk taxa; increased surveillance at Florida's ports, state borders, and high‐risk pathways; and periodic review and revision of the list. Few horizon scans detail the comprehensive methodology (including list‐building), certainty estimates for all scoring categories and the final score, detailed pathways, and the magnitude and mechanism of impact. Providing this information can further inform prevention efforts and can be efficiently replicated in other regions. Moreover, harmonizing methodology can facilitate data sharing and enhance interpretation of results for stakeholders and the general public.